2018
DOI: 10.1159/000489608
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Adolescents Referred to a Gender Clinic: Are Youth Seen Now Different from Those in Initial Reports?

Abstract: Background/Aims: To examine characteristics, including mental health comorbidities, among adolescents presenting to a transgender clinic and to compare these data to previous reports. Methods: Retrospective chart review among youth seen at The Hospital for Sick Children between January 2014 and June 2016. Demographic data, clinical characteristics, and mental health comorbidities were assessed. Baseline and repeat blood work were also examined. Results: Charts from 203 adolescents aged 12–18 years were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 35 publications
5
43
1
1
Order By: Relevance
“…So far, one study has examined whether adolescents (N = 203) who were referred to a gender clinic in recent years were different from those in initial reports [18]. In contrast to initial studies, it was found that more birthassigned females than birth-assigned males applied.…”
Section: Introductionmentioning
confidence: 96%
“…So far, one study has examined whether adolescents (N = 203) who were referred to a gender clinic in recent years were different from those in initial reports [18]. In contrast to initial studies, it was found that more birthassigned females than birth-assigned males applied.…”
Section: Introductionmentioning
confidence: 96%
“…Gender-incongruent (GI) youth often experience gender dysphoria, the distress resulting from the discordance between birth-assigned and experienced gender. 1 These youth face higher rates of mental health problems (including mood and anxiety disorders, self-harm, suicidal ideation, and suicide attempts) [2][3][4][5][6][7][8] than gender-congruent youth. 9,10 GI youth are also more likely to be hospitalized 9 for mental health concerns compared with their gender-congruent peers.…”
mentioning
confidence: 99%
“…12,13 Despite these benefits, reports of GI youth seeking GAMC demonstrate that some youth present to care later in adolescence with more pubertal development. [2][3][4][5]14 It is possible that presentation at earlier ages may be associated with fewer mental health concerns. We are aware of one study in which researchers address this question directly: Holt et al 7 reported that youth referred to a gender clinic at age $12 were more likely to have suicidal ideation and attempts, selfharm, and low mood and/or depression than those referred at younger ages.…”
mentioning
confidence: 99%
“…Recent studies have suggested a change in the sex ratio of adolescents presenting to transgender clinics, with many more youth who are assigned female gender at birth seeking care than those assigned male. [50][51][52] One clinic reported that more than 85% of patients seeking to transition were assigned female gender at birth. 20 A recent Canadian national survey also found a higher proportion of people assigned female gender at birth seeking to transition.…”
Section: What Are the Gaps In Knowledge?mentioning
confidence: 99%
“…The likely underrepresentation of minority ethnic and Indigenous youth is one area deserving of much further attention. 52 Practically speaking, the intersection of multiple identities (e.g., ethnicity, race, socioeconomic privilege, geographical location), medical and psychological comorbidities, and transgender identity will affect the resources suggested to youths and their families. Specialized youth groups and mental health organizations may have experience working with these unique populations.…”
Section: What Are the Gaps In Knowledge?mentioning
confidence: 99%